Reports about violence, concepts of violence and teachers’ classroom practices - Souza, Liliane Viana de; Ristum, Marilena (Paidéia (Ribeirão Preto), 2005)
This work aimed at analyzing the teacher's reports of violence events; to associate these reports to their concepts of violence and classroom practices, and to compare public and private schools teachers considering their reports. Forty seven public and private schools teachers were interviewed. According to the reports of violence events occurred in the school, the violent actions practiced by pupils were more common, and in the reports of violence in the neighborhood, the delinquency actions predominated. The triangular relation among reports, violence concept and teacher's practices indicated that those reports confirm somehow the results on the concepts of violence as well as on the teacher's practices. Although they have provided an important complementary picture to the understanding of teachers' violence concept, the reports were insufficient to meet all dimensions of this concept.